Butterfly fauna (Lepidoptera, Papilionoidea) in an ecotone between two biodiversity hotspots in Minas Gerais, Brazil - Soldati, Déborah; Silveira, Fernando Amaral da; Silva, André Roberto Melo (Papéis Avulsos de Zoologia, 2019)
This paper investigates the butterfly fauna of the ‘Serra do Rola-Moça’ State Park, Minas Gerais, Brazil. We evaluate i) the seasonal variation of species richness and composition; and ii) the variation in composition of the local butterfly assemblage among three sampling sites and between the dry and rainy seasons. Sampling was carried out monthly between November 2012 and October 2013, using entomological nets. After a total sampling effort of 504 net hours, 311 species were recorded, one of them endangered in Brazil, and eight probable new species. Furthermore, two species were new records for the region and seven considered endemic of the Cerrado. There was no significant difference in species richness between the dry and the rainy seasons, however the species composition varies significantly among sampling sites. Due to its special, heterogeneous environment, which is home to a rich butterfly fauna, its preservation is important for the conservation of the regional butterfly fauna.